Comprehensive assessment of Gran Canaria water-energy-food nexus with GIS-based tool. (10th November 2021) - Borge-Diez, David; García-Moya, Francisco José; Rosales-Asensio, Enrique
Abstract: Society's increasing demand for resources creates an urgent need of resource allocation strategies. This research analyzed how alternative renewable-based energy plans affect a sustainability index related to the Water-Energy-Food nexus in a region highly dependent on desalted water. 50 water bodies of the island of Gran Canaria were analyzed for evaluating a pumping hydro energy storage strategy to support a renewable energy plan. The storage uses water from desalination plants which allowed to increase water and energy in the system. With the restrictions imposed, the Spanish island of Gran Canaria could store from 11.44 GWh/mcm to 30.76 GWh/mcm. Results showed that, depending on the specific renewable energy plan and on the factor of operation in the desalination plant, the stress in the water subsystem would be reduced from 8 mcm to 20 mcm. A system analysis strategy to control the water index was proposed to support the decision-making strategies. Graphical abstract: Image 1 Highlights: How renewable energy plans affect Water-Energy-Food sustainability index in islands. Pumping storage systems using water for desalination are studied in Canary Islands. In Gran Canaria could be stored from 1144.15 MWh/0.1 Hm 3 to 3076 MWh/0.1 Hm 3 Proposal reduces the stress in the water subsystem would from 8 Hm 3 to 20 Hm 3 Water index analysis strategy is proposed to support the decision-making strategies.